APPROACHING THE GOLDEN MONTH OF RAMADAN - Usman Jimoh Muhammad (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
Out of the twelve lunar months, the paper ranks the month of Ramadan as a golden opportunity for the Muslims. It is in this regard that the paper postulates the need to prepare well for it in order to annex the bountiful opportunities in it. The paper is divided into six sections. Section one deals with the introduction, chapter two identifies the reasons why Ramadan is a precious month for the Muslims. In section three, an effort is made to explain the necessity for proper preparation in attainment of desired goal of whichever type. In section four, readiness to withdraw from sin, readiness to perpetually overcome the devil and readiness to resolve malice are some of the requisite tools for the attainment of a fruitful Ramadan. The paper recommends Muslims to reflect on the issues discussed in the paper and embark on self adjustment where needed.